Antileishmanial and antitrypanosomal activity of symmetrical dibenzyl-substituted α,β-unsaturated carbonyl-based compounds - Alkhaldi AAM; de Koning HP; Bukhari SNA (Dove Medical Press, 2019)
Abdulsalam AM Alkhaldi,1 Harry P de Koning,2 Syed Nasir Abbas Bukhari31Biology Department, College of Science, Jouf University, Sakaka, Aljouf 2014, Saudi Arabia; 2Institute of Infection, Immunity and Inﬂammation, College of Medical, Veterinary and Life Sciences, University of Glasgow, Glasgow G12 8TA, UK; 3Department of Pharmaceutical Chemistry, College of Pharmacy, Jouf University, Sakaka, Aljouf 2014, Saudi ArabiaBackground: Human African Trypanosomiasis (HAT) and leishmaniasis are two of the most neglected challenging tropical diseases, caused by the kinetoplastid parasites Trypanosoma and Leishmania species, respectively. For both of these complex disease spectra, treatment options are limited and threatened by drug resistance, justifying urgent new drug discovery efforts.Purpose: In the present study we investigated the antitrypanosomal and antileishmanial activity of a series of 21 symmetrical α,β-unsaturated carbonyl-based compounds, each featuring two 3-methoxybenzene attached to a central cyclohexanone, tetrahydro-4-pyranone scaffold or 4-piperidone ring. Structure-activity relationships were explored with respect to substitution on positions 3, 4 and 6 of the terminal 3-methoxybenzyl groups, and seven types of central ring.Results: Compounds 3a, 3o, 3s and 3t, showed broad anti-kinetoplastid activity against all species and strains tested.Conclusion: Compound 3o featuring N-methyl-4-piperidone was found to be the most potent analog and therefore can serve as a potential lead for the development of new drug candidates for trypanosomiasis and leishmaniasis.Keywords: protozoan parasites, sleeping sickness, -α,β-unsaturated carbonyl-based compounds, cyclohexanone, piperidine